PROFIL KEMAMPUAN SISWA SMP DALAM MENYELESAIKAN SOAL UJI KOMPETENSI LABORATORIUM (UKL) PADA KEGIATAN PEKAN RAYA BIOLOGI (PRB) 2016 - Banjarnahor, Jelida; Natalina, Mariani; ', Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Â Abstract : The purpose of this study is to know the ability Profile Junior high school students in Problem Solving Competency Test Laboratory (UKL) On Activity Fair Biology (PRB) in 2016. The research was conducted at the campus of the University of Riau FKIP Biology Education and Junior High School in Pekanbaru that follow Fair Biology ( PRB) in July and October 2016. the sample in this study were all participants Competency Test Laboratory (UKL) totaling 47 people.Techniques in the determination of sample is total sampling. Data collection instruments used in the form of question and answer sheets UKL student participants. The measured parameter is the analysis of items, based on cognitive abilities and psychomotor student.The results show the ability of junior high school students in solving Competency Testing Laboratories based on a set of cognitive domains I shows the criteria are not well with the average of 13.7% and II showed less criteria set well with the average of 24.7% and for psychomotor on set I showed sufficient criteria both with average 42.15% and II showed less criteria set well with the average of 38.5%. The conclusion of the research is the competence profile junior high school students in solving Competency Test Laboratory (UKL) on the activities of the Fair Biology (PRB) in 2016 was less good.